Professional self –realisationof the university teacher isthekey to the quality of education - Томаз, І. А. (Scientific notes of the pedagogical department, 2018)
The article deals with the essence of professional self-realization notion of a teacher of a higher educational institution. The importance of his/her professional self-identification is proved. As the title implies the article describes the   specialist formation problem as the process  of personality progressive development under the influence of advanced pedagogical experience, professional  and personal activities, aimed at self-improvement and self-realization in order to achieve the modern level of education. Education quality indicators, which will help to make  educational process in higher educational institutions to become more targeted are pointed out.  Levels of self-realization: initial professional development, professional adaptation and further direct self-realization of teachers, which will help specialists  plan the process of their professional growth are revealed. It is noted that the readiness of a teacher to adaption depends on the level of necessary knowledge, abilities, skills and qualities that he/she has. Much attention is given to the  strategy of the formation of a teacher  and the process of his/her self-realization. The main problem of the article is to prove that a key figure in a high-quality educational process at the university is a teacher, and the effective way of revealing his/her personal and professional potential is the process of professional growth, competence and self-realization. It is particularly noted that the improvement of professional skills and the development of creative potential, the acquisition of innovations and advanced teaching technologies ultimately increase the efficiency and quality of the educational process.The algorithm  of the successive activity process of the teacher towards self-realization is developed. The article is intended for teachers of higher educational institutions.It contains information about the quality of education and the process of self-realization of the teacher. In addition, the article is of interest  to the teachers of comprehensive secondary schools and specialized educational institutions. The directions of further scientific research of the stated problem are determined.